Magnetic Waves Excited by Newborn Inner-source Pickup H+ Measured by the Voyager Spacecraft Inside 3 au - Sophia J. Hollick; Charles W. Smith; Zackary B. Pine; Matthew R. Argall; Colin J. Joyce; Philip A. Isenberg; Philip R. Quinn; Bernard J. Vasquez; Nathan A. Schwadron; Justyna M. Sokół; Maciej Bzowski; Marzena A. Kubiak (The Astrophysical Journal, 2025)
In S. J. Hollick et al., we surveyed the Voyager magnetic field data from launch through 1990 where the Voyagers 1 and 2 spacecraft reach 43.5 au and 33.6 au, respectively. We identified 637 intervals of wave activity that could be attributed to either interstellar pickup He ^+ , H ^+ , or both. In our quest to identify and study low-frequency magnetic waves arising from interstellar pickup H ^+ , we found 19 intervals, 16 with thermal ion data, within ∼3 au. We compared the growth rate of the waves with the rate of background turbulence they must overcome to reach observable levels. Ionization of interstellar neutral H is highly efficient, resulting in a factor of 10 reduction in density by 1 au relative to values at R  > 10 au. At the same time, solar wind turbulence increases with decreasing distance to the Sun. This makes it unlikely that interstellar neutral hydrogen can penetrate within ∼3 au in sufficient number to explain the wave observations seen by the Voyager magnetometers. We consider the possibility that the so-called “inner source” for pickup H ^+ arising from the interaction of solar wind protons with dust grains may account for the density of newborn pickup ions required for the growth of the observed waves. Although the Voyagers lack the instrumentation required to measure pickup ions, we do conclude that the inner-source theories provide a compelling explanation for the majority of the observations while it is possible that a few could be due to either interstellar ions or shocks.